2003
DOI: 10.1046/j.1365-2435.2003.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and the chemical composition of poikilothermic organisms

Abstract: Summary 1.Temperature strongly affects virtually all biological rate processes, including many central to organismal fitness such as growth rate. A second factor related to growth rate is organismal chemical composition, especially C : N : P stoichiometry. This association arises because high rates of growth require disproportionate investment in N-and P-rich biosynthetic cellular structures. Here the extent to which these factors interact is examined -does acclimation temperature systematically affect organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
225
4
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(259 citation statements)
references
References 58 publications
28
225
4
2
Order By: Relevance
“…With increasing temperature, algal C:nutrient ratios have been shown to increase, either due to enhanced carbon fixation per unit resource (e.g. Moorthi et al 2016) or due to decreasing intracellular N and P concentrations based on enhanced efficiency of RNA (requiring P) and proteins (requiring N) in biochemical reactions (Woods et al 2003). Also, the contribution of photosynthesis and phagotrophy varies with temperature in mixo trophs (Wilken et al 2013, Princiotta et al 2016, which presumably also alters intracellular nutrient stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing temperature, algal C:nutrient ratios have been shown to increase, either due to enhanced carbon fixation per unit resource (e.g. Moorthi et al 2016) or due to decreasing intracellular N and P concentrations based on enhanced efficiency of RNA (requiring P) and proteins (requiring N) in biochemical reactions (Woods et al 2003). Also, the contribution of photosynthesis and phagotrophy varies with temperature in mixo trophs (Wilken et al 2013, Princiotta et al 2016, which presumably also alters intracellular nutrient stoichiometry.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, higher absolute levels of enzymes would increase reaction rates at all temperatures. In support of this, a literature survey found that cold-acclimated ectotherms contained higher cell-specific levels of phosphorus (P) and rRNA than warm-exposed conspecifics (Woods et al 2003). This is probably due to reduced efficiency of protein synthesis at low temperatures, i.e.…”
Section: Introductionmentioning
confidence: 91%
“…A crucial question is how animals cope with the need for high growth rates due to short seasons in cold areas, i.e. how can ectothermic animals maintain relatively high rates of growth and metabolism despite living at low temperatures (Woods et al 2003). Two hypotheses may explain thermal adaptations in cellular processes: structural changes of enzymes that increase the rate of reaction at low temperature (cold adaptation, Hochachka and Somero 1973), or higher absolute levels of enzymes in cells in support of overall reaction rates (Adamowicz et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The elements carbon (C), nitrogen (N), and phosphorus (P) are the fundamental chemical elements of an organism. The stoichiometry of an organism is closely related to the important ecological processes such as ecosystem species composition and diversity, adaptation of organisms to environmental stress, and interspecific relationships (Venterink et al 2003;Woods et al 2003;Aerts et al 2003;Güsewell et al 2005).…”
Section: Introductionmentioning
confidence: 99%